«A hand for sword – a heart for Lady»: the interpretation of love in the North French knightly romance - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the analysis of the preconditions for the formation of a hypothetical model of love in a knightly medieval culture. The axiological shifts in the development of Middle Ages culture, that led to the transformation of the knightly culture in the direction of secular form, are revealed.
Keywords: chivalry; knightly culture; honor code; urban culture; aristocratic court; novel; knightly romance; lyrical and heroic utopia; the hypothetical model of knightly love